2016
DOI: 10.1021/acs.jpca.6b08405
|View full text |Cite
|
Sign up to set email alerts
|

Improved Flavin-Based Catalytic Photooxidation of Alcohols through Intersystem Crossing Rate Enhancement

Abstract: The triplet excited-state formation efficiency in a flavin derivative was increased by the introduction of iodine into the molecular framework. The transient absorption measurements showed that the intersystem crossing rate was 1.1 × 10(10) s(-1), significantly faster than in the parent flavin compound. Furthermore, the photocatalytic efficiency of iodoflavin was evaluated using the oxidation of benzyl alcohol as a model reaction. The benzaldehyde product yields were higher when iodoflavin was used as a photoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 33 publications
1
39
0
Order By: Relevance
“…In 2016, Glusac and co-workers reported C9-iodoflavin 29 which benefits from a drastically faster intersystem crossing (ISC) to the triplet state after photoexcitation (Figure 7A). 69 They demonstrated that this heavy atom effect made 29 a more active catalyst for the oxidation of benzyl alcohol to benzaldehyde when compared to the unsubstituted analogue. Similar observations were made by Zhao, Guo, and co-workers who reported the C7,C8-dibrominated flavin 30, again with the intention to benefit from the heavy atom effect (Figure 7B).…”
Section: C6-c9-modificationmentioning
confidence: 99%
“…In 2016, Glusac and co-workers reported C9-iodoflavin 29 which benefits from a drastically faster intersystem crossing (ISC) to the triplet state after photoexcitation (Figure 7A). 69 They demonstrated that this heavy atom effect made 29 a more active catalyst for the oxidation of benzyl alcohol to benzaldehyde when compared to the unsubstituted analogue. Similar observations were made by Zhao, Guo, and co-workers who reported the C7,C8-dibrominated flavin 30, again with the intention to benefit from the heavy atom effect (Figure 7B).…”
Section: C6-c9-modificationmentioning
confidence: 99%
“…47 Heavy atom substitution has been shown to improve both the rate of ISC and the singlet oxygen quantum yield (ФΔ) in flavin derivatives used for synthetic photooxidation reactions. 48,49 Although the heavy-atom effect has been used to boost photodynamic efficacy for other PS dyes in PDI applications, it has not yet been explored for flavin derivatives. 50,51 To afford both methylated (F1-2) and brominated derivatives (F3-4), a Boc-protected ethylene amino component was first installed to the methylated or brominated arene core prior to cyclisation of the isoalloxazine ring system.…”
Section: Synthesis and Characterisation Of Flavinsmentioning
confidence: 99%
“…This dual catalysis involves a photooxidation cycle and a dark organocatalytic cycle, and uses a specific synthetic flavinium salt that exhibits a high photoexcited oxidation potential above +2.5 V (Figure ). The use of flavin derivatives as photocatalysts has led to the modification of the core scaffold with the goal of improving the photophysical properties such as rate of intersystem crossing and long‐lived charge separation (Figure ) …”
Section: Bioinspired Catalysis Using Flavin Redox Cofactorsmentioning
confidence: 99%
“…[49] This dual catalysis involves a photooxidation cycle and a dark organocatalytic cycle, and uses a specific synthetic flavinium salt that exhibits a high photoexcited oxidation potential above + 2.5 V (Figure 4). The use of flavin derivatives as photocatalysts has led to the modification of the core scaffold with the goal of improving the photophysical properties such as rate of intersystem crossing [50] and long-lived charge separation (Figure 4). [51] Beyond dual catalysis, supramolecular or nanoscale systems can be achieved through modification of the flavin core scaffold with dedicated subunits to combine flavin-based features with properties such as anion-binding with crown ethers, [52,53] and substrate-binding sites with cyclodextrin [54] and zinc(II)-cyclen.…”
Section: Bioinspired Catalysis Using Flavin Redox Cofactorsmentioning
confidence: 99%